The Language of Police Reports: A Quest for Precision or a Bureaucratic Exercise of Language Degradation - Ćetković, Sanja (Círculo de Lingüística Aplicada a la Comunicación, 2017)
The language of the members of law enforcement has been widely studied mostly in terms of investigating various aspects of police interview discourse. However, our aim here is to examine the language of police reports as a sample of written language of the police outside the context of police-suspect encounters and to describe some of its distinctive linguistic features which function as more or less effective means for achieving maximum clarity and precision. An intimate relationship between the language of legal documents and the language of police reports has been established with respect to style and specific language choices that characterize both registers. Nevertheless, we have observed some peculiar features of police written language that seem to be originating from a compelling need to be as accurate and all-inclusive as possible and to fully conform to conventional standards of report writing.